Response of Growth and Yield of Soybean to Urea Application Frequency and Coffee Husk Compost Dosage in Coastal Land - Sirateman, Selamat; Pujiwati, Hesti; Widodo; Gusmara, Herry; Sudjatmiko, Sigit; Prameswari, Wuri (TERRA : Journal of Land Restoration, 2024)
Utilizing marginal land, such as coastal areas, offers a viable approach to increasing soybean production. However, coastal lands are often characterized by low nutrient content and high porosity, necessitating effective strategies to optimize crop growth and yield. This study aimed to examine the interaction between urea application frequency and coffee husk compost dosage, identifying the best combination for enhancing soybean performance on coastal land. The research was conducted from November 2023 to February 2024 in Bengkulu City, Indonesia, at an elevation of approximately 5 meters above sea level. A Randomized Complete Block Design (RCBD) was employed with two factors: coffee husk compost dosage (0, 10, 20, and 30 tons ha-1) and urea application frequency (0,1,2,and 3 times,at 100 kg ha-1). Results revealed a significant interaction between compost dosage and urea frequency, influencing several growth parameters, including plant height, pod number per plant, fresh and dry shoot weight, fresh and dry root weight, and seed weight per plant. Compost doses of 20 and 30 tons ha-1, along with 2 or 3 applications of urea, notably increased leaf number, productive branch number, and seed yield per plant. These findings indicate that optimizing both urea application frequency and coffee husk compost dosage can significantly improve soybean productivity on nutrient-poor coastal soils. This highlights the importance of integrated nutrient management for enhancing crop yield in marginal environments.